Intra-renal and subcellular distribution of the human chloride channel, CLC-5, reveals a pathophysiological basis for Dent's disease. - Devuyst, O; Christie, P; Courtoy, P; Beauwens, R; Thakker, R (Oxford University Press, 1999)
Dent's disease, which is a renal tubular disorder characterized by low molecular weight proteinuria, hypercalciuria and nephrolithiasis, is associated with inactivating mutations of the X-linked chloride channel, CLC-5. However, the manner in which a functional loss of CLC-5 leads to such diverse renal abnormalities remains to be defined. In order to elucidate this, we performed studies to determine the segmental expression of CLC-5 in the human kidney and to define its intracellular distribution. We raised and characterized antisera against human CLC-5, and identified by immunoblotting an 83 kDa band corresponding to CLC-5 in human kidney cortex and medulla. Immunohistochemistry revealed CLC-5 expression in the epithelial cells lining the proximal tubules and the thick ascending limbs of Henle's loop, and in intercalated cells of the collecting ducts. Studies of subcellular human kidney fractions established that CLC-5 distribution was associated best with that of Rab4, which is a marker of recycling early endosomes. In addition, confocal microscopy studies using the proximal tubular cell model of opossum kidney cells, which endogenously expressed CLC-5, revealed that CLC-5 co-localized with the albumin-containing endocytic vesicles that form part of the receptor-mediated endocytic pathway. Thus, CLC-5 is expressed at multiple sites in the human nephron and is likely to have a role in the receptor-mediated endocytic pathway. Furthermore, the functional loss of CLC-5 in the proximal tubules and the thick ascending limbs provides an explanation for the occurrences of low molecular weight proteinuria and hypercalciuria, respectively. These results help to elucidate further the patho-physiological basis of the renal tubular defects of Dent's disease.